Country-specific determinants of FDI inflows to the MENA region: A systematic review and future research directions. Issue 1 (3rd February 2020) - Dimitrova, Anna; Rogmans, Tim; Triki, Dora
Abstract : Purpose: This paper aims to synthesize, analyze and categorize the empirical literature on country-specific factors that affect foreign direct investment (FDI) inflows to the Middle East and North Africa (MENA) region. Identifying gaps and methodological challenges in the reviewed articles, recommendations are made to guide future research. Design/methodology/approach: Applying the systematic review methodology, content analysis is conducted of 42 relevant empirical studies that explore country-specific FDI determinants in the MENA region during the period 1998–2018. Findings: This review study identifies four main research gaps in the extant literature: a lack of consensus on a common definition of the MENA region and a weak understanding of the specificities of its investment environment; a limited set of FDI theories used and a lack of other theoretical perspectives; a recurrent focus on the direct relationship between host country–specific determinants and FDI, thus ignoring the moderating and mediating effects of some variables; and the absence of certain country-specific factors pertaining to the MENA countries. Originality/value: This study contributes to the international business field by enhancing our understanding of the FDI determinants in emerging and developing markets, especially the MENA countries. It develops a typology of FDI country-specific factors in the MENA region based on four main categories: macroeconomic and financial, institutional and regulatory, natural resource endowment and socio-cultural. Paths for future research are suggested.